A Multi-Tissue, Multi-Species Assessment of Lipid and Urea Stable Isotope Biases in Mesopredator Elasmobranchs - Bennett-Williams, Joshua; Skinner, Christina; Wyatt, Alex S. J.; McGill, Rona A. R.; Willis, Trevor J. (Frontiers in Marine Science, 2022)
The application of stable isotope analysis (SIA) is increasing in elasmobranch trophic ecology, but inconsistency remains in terms of the tissue pre-treatment methods chosen to remove biases introduced by lipids and urea. SIA of a range of non-lethally extracted tissues from a diverse group of elasmobranchs, including mesopredators, is increasing, yet most studies assume that isotope biases from lipid and urea are the same across tissues and species. To determine tissue- and species-specific isotope biases across treatment methods, four tissues (muscle, fin, plasma, and red blood cells (RBC)) were non-lethally extracted from three mesopredator elasmobranch species and subjected to one of three treatment methods: rinsing with 1) deionized water [DW], 2) chloroform/methanol [LE], or 3) deionized water followed by chloroform/methanol [DW+LE]. Slight muscle δ13C increases with LE and DW+LE suggested lipid removal, while large muscle δ15N increases across all treatments indicated removal of urea. In fin, δ13C values decreased with DW but increased with LE and DW+LE, whilst all treatments increased fin δ15N, suggesting removal of both lipid and urea. Plasma δ13C and δ15N displayed high individual variation with large decreases in δ13C across all treatments, but particularly DW, suggesting the removal of 13C-enriched compounds. A small increase in plasma δ15N across all treatments suggested minimal urea removal. In RBC, all treatments showed small δ13C declines, with no difference in δ15N, suggesting minimal removal of 13C-enriched compounds and urea. For muscle and fin, DW+LE is the most appropriate treatment to standardise δ13C and δ15N consistently across individuals and tissues. The large individual variation in treatment effects on plasma suggests it is unsuitable for current treatment methods. The consistent treatment effects for RBC allow for DW+LE standardisation, however, broader species-specific effects are unknown. The importance of treatment choice for accurately estimating prey contributions to elasmobranch diet was highlighted using Bayesian stable isotope mixing model comparisons, with prey contributions varying significantly among treatments. This variability suggests that ecological inferences from elasmobranch tissues SIA are not robust to different treatment methods. It is recommended that studies employ standardised corrections using a combined DW+LE treatment where applicable.